2013
DOI: 10.1002/jcp.24248
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin induces stromal cell‐derived factor‐1 expression by β1 integrin signaling in colorectal cancer cells

Abstract: Obesity has been shown to be associated with the risk of colorectal cancer (CRC). Adipokines produced by the adipose tissue are linked to some malignancies, including CRC. Visfatin is an adipokine shown to be a biomarker of CRC malignant potential. In addition, the stromal cell-derived factor-1 (SDF-1) has been reported to play a role in CRC progression. Although the relationship between visfatin and CRC has been established, the underlying mechanism has not been clarified. We investigated the molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 41 publications
2
32
0
1
Order By: Relevance
“…The relation of visfatin to colorectal cancer (CRC) is among the best characterized to date [94][95][96], but data supporting its role in breast cancer or postmenopausal breast cancer (BC/PBC) is increasing [97]. Research also demonstrates a role of visfatin in ovarian cancers [98].…”
Section: Visfatinmentioning
confidence: 99%
See 4 more Smart Citations
“…The relation of visfatin to colorectal cancer (CRC) is among the best characterized to date [94][95][96], but data supporting its role in breast cancer or postmenopausal breast cancer (BC/PBC) is increasing [97]. Research also demonstrates a role of visfatin in ovarian cancers [98].…”
Section: Visfatinmentioning
confidence: 99%
“…Specifically, CRC cells express chemokine receptors, CXCR4 and CXCR7, both of which can bind SDF-1 that promotes survival and migration of the cancerous cells [101,102]. Wen-Shih Huang et al [96] demonstrated that increased production of visfatin leads to increased expression of SDF-1. This is mediated by the B1 integrin and involves signaling through the ERK and p38 MAPK pathways [96].…”
Section: Visfatinmentioning
confidence: 99%
See 3 more Smart Citations